The Effect of The Course Review Horay Learning Model on Critical Thinking Skills of Grade V Students in Elementary Schools - Fatmawati, Fatmawati; Miranda, Ayu; Reza, M Fachru; Handayani, Rizki; Yusrizal, Yusrizal (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to identify, find out how influential the CRH learning model is based on students' critical thinking skills. This research is a quasi-experimental research using pre-test and post test control group design. With 40 students from grade V SD Negeri 107406 Cinta Rakyat who became the study population using two different classrooms as experimental classes and control classes, each class consisting of 20 students. Using the technique the total sample from this study was taken, and used on all populations as its sample. This research tool uses a research test consisting of 20 essay questions. The data collected was obtained through student learning outcomes from before and after the test. In addition, the data was also analyzed using Normality test analysis, Homogeneity test, and continued with T-test samples. Then obtained with a significant value of 0.011 > 0.05 which has a difference of about 9.5 which means accepting H0 and rejecting Ha, from these results researchers concluded that using the CRH method can affect students' critical thinking.